99mTc-labeled therapeutic inhaled amikacin loaded liposomes. (December 2013) - Lee, Jae-Ho; Cheng, Kenneth T.; Malinin, Vladimir; Li, Zhili; Yao, Zhengsheng; Lee, Sung-Jin; Gould, Christine M.; Olivier, Kenneth N.; Chen, Clara; Perkins, Walter R.; Paik, Chang H.
Abstract The radiolabeling of the liposome surface can be a useful tool for in vivo tracking of therapeutic drug loaded liposomes. We investigated radiolabeling therapeutic drug (i.e. an antibiotic, amikacin) loaded liposomes with 99mTc, nebulization properties of 99mTc-labeled liposomal amikacin for inhalation (99mTc-LAI), and its stability by size exclusion low-pressure liquid chromatography (LPLC). LAI was reacted with 99mTc using SnCl2 dissolved in ascorbic acid as a reducing agent for 10 min at room temperature. The labeled products were then purified by anion exchange resin. The purified 99mTc-LAI in 1.5% NaCl solution was incubated at 4 °C to assess its stability by LPLC. The purified 99mTc-LAI was subjected to studies with a clinically used nebulizer (PARI eFlow®) and the Anderson Cascade Impactor (ACI). The use of ascorbic acid at 0.91 mM resulted in a quantitative labeling efficiency. The LPLC profile showed that the liposomal peak of LAI detected by a UV monitor at both 200 nm and 254 nm overlapped with the radioactivity peak of 99mTc-LAI, indicating that 99mTc-LAI is suitable for tracing LAI. The ACI study demonstrated that the aerosol droplet size distribution determined gravimetrically was similar to that determined by radioactivity. The liposome surface labeling method using SnCl2 in 0.91 mM ascorbic acid produced 99mTc-LAI with a high labeling efficiency and stability that are adequate to evaluate the deposition and clearance of inhaled LAI in the lung by gamma scintigraphy.